Analysis of damping from vertical sloshing in a SDOF system. (1st May 2021) - Constantin, L.; De Courcy, J.; Titurus, B.; Rendall, T.C.S.; Cooper, J.E.
Graphical abstract: Highlights: Vertically vibrating transient tests demonstrate additional sloshing-induced damping. Vertical motion shows different piecewise linearly damped regimes. Coupled simulations demonstrate good comparisons with the experimental results. Abstract: The effect of the sloshing motion of liquid in a tank on the vertical transient motion of a single degree of freedom system is investigated. Step release tests of a vertically vibrating structure, including a tank containing liquid, demonstrate that added damping from the sloshing motion depends upon the amount of fluid in the tank and the maximum acceleration. The maximum amount of damping was observed at a 50% fill level and the system showed three distinct response regimes during the transient decay, all related to different motions of the fluid. The first response regime, immediately at the start of the transient, is considered to be the most important to exploit for aircraft gust loads alleviation due to its dominant role in the overall energy dissipation balance. Further, to advance the understanding of the modelling and predictive capabilities, coupled fluid-structure models of two opposing levels of fidelity were developed and evaluated. Namely, smoothed particle hydrodynamics (SPH) and an equivalent mechanical model (EMM) based on a bouncing ball model were considered to represent the fluid motion in the tank during the experiment. Both models are shown to provide good predictive capability in the initial impacting sloshing mode while the subsequent flow regime can be predicted with the SPH model only. The findings in this paper open routes towards improved coupled fluid-structure models and their use in improved aeroelastic wing design.